Occupation safety and health in local and international standard forms of construction contract - Goh, P.H (Universiti Malaysia Sarawak, UNIMAS, 2009)
The Malaysia government and other authoritative bodies or institutions have put in substantial amount of effort in the implementation of Occupational Safety and Health (hereafter, OSH) in the local construction industry so as to minimize the rate of accidents as well as enhancing a safe and healthy working environment to the workers and the public. However, the effectiveness of such efforts is yet to be confirmed. The aim of this research is to study the construction contract clauses in relation to the current OSH practice in the local and international Standard Forms of Construction Contracts, namely the PWD Form 203A (Rev.2007), PAM Contract 2006 (With Quantities), CIDB 2000 and AS (2124 – 1992). The clauses are classified into four (4) main aspects that are the indemnity provision, insurance provision, workmen provision and lastly safety provision. Comparisons are made for these four (4) aspects in detail as well as their comprehensiveness, completeness, procedures, and equal provision. Interviews are also conducted to obtain opinions from the local construction participants to learn their perceptions of the OSH practice and Standard Forms of Construction Contracts. Through this research, it is hoped that a clearer picture of what the real construction workplace needs or lack of can be obtained; and to acknowledge to what extent our contract forms had catered for OSH; and to further find ways to use construction contract forms as a mean to improve the insufficiency of OSH practice in our local construction industry.